Benjamin's passages : dreaming, awakening - Gelley, Alexander (Fordham University Press, 2015)
In transposing the Freudian dream work from the individual subject to the collective, Walter Benjamin projected a 'macroscosmic journey' of the individual sleeper to 'the dreaming collective, which, through the arcades, communes with its own insides'. This book examines the figurative status of sleeping and awakening within the allegorical structure of The Arcades Project and in Benjamin's thought more broadly.